Mathematical Problem Solving and Disposition: Experiment with Tenth Grade Students Using MEAs - Mellyana Mellyana; Utari Sumarmo; Asep Kustiana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This reseach is a pre test-post test experimental control group design having a goal to examine  the role of Model Eliciting Activities (MEAs) approach, on student’s mathematical problem solving ability (MPSA) and disposition (MD). The research involved 59 tenth grade students of a Senior High School in Garut Inodonesia, a MPSA test, and a  MD  scale. The research  found MEAs took greater role than SA on improving student’s MPSA and its N<Gain>.  Students getting treatment with MEAs obtained MPSA higher grade than the grade of students taught by SA, however those both grades were at low grade level, and students encountered many difficulties on solving MPSA tasks. In addition to,  there were no different grades on student’s MD, and the grades were at fairly good level, and there was strong association between MPSA and MD. Other findings was that  students declared positive opinion on MEAs  and they peformed active learning during the lessons. Keywords:mathematical problem solving, disposition, MEAs approach,